2004
DOI: 10.1007/s00213-004-1983-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of reboxetine and citalopram on hand-motor function in patients suffering from major depression

Abstract: Our findings are in line with the hypothesis that SSRI tend to have small, but more pronounced negative effects on motor function than NARI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…These effects were associated with an enhancement of cortical excitability as tested by transcranial magnetic stimulation (TMS). In line with these results, a recent study in patients with a major depression (Hegerl et al 2005) indicated more favorable effects of a 4-week treatment with RBX on motor function (handwriting) than with the selective serotonin reuptake inhibitor citalopram. Nevertheless, earlier studies using relatively low single doses of RBX (0.5-4 mg) have shown no significant beneficial influences on psychomotor performance or cognitive function (Kerr et al 1996;Herrmann and Fuder 1998).…”
Section: Introductionmentioning
confidence: 60%
“…These effects were associated with an enhancement of cortical excitability as tested by transcranial magnetic stimulation (TMS). In line with these results, a recent study in patients with a major depression (Hegerl et al 2005) indicated more favorable effects of a 4-week treatment with RBX on motor function (handwriting) than with the selective serotonin reuptake inhibitor citalopram. Nevertheless, earlier studies using relatively low single doses of RBX (0.5-4 mg) have shown no significant beneficial influences on psychomotor performance or cognitive function (Kerr et al 1996;Herrmann and Fuder 1998).…”
Section: Introductionmentioning
confidence: 60%
“…Aberrant motor activity in MDD includes psychomotor retardation, agitation, reductions in facial expression as well as slowing of fine motor skills, gait and speech (Krane-Gartiser et al, 2014;Lemke et al, 1999;Michalak et al, 2009;Volkers et al, 2003;Walther et al, 2011). Hand-motor tasks have been used to assess the impact of psychopharmacological treatment on motor function in depression (Hegerl et al, 2005;Mergl et al, 2007), while longitudinal changes in spontaneous motor behavior have been proven useful to monitor treatment outcomes. In the latter context, the use of wrist actigraphy allows continuous recording of various parameters of motor activity in naturalistic settings (Stanley, 2003;Todder et al, 2009;Volkers et al, 2002;Walther et al, 2012bWalther et al, , 2009aWalther et al, , 2009bWalther et al, , 2009c, yielding quantitative measures of the clinical phenomenon under scrutiny.…”
Section: Background/introductionmentioning
confidence: 99%
“…The technique affords objective and real-time recordings of perceptual motor activity and allows the distinction of the cognitive and motor processes involved in a writing movement. Hegerl et al [7] and Mergl et al [8] who had their depressed samples perform such computerized copying tasks during a 4-week treatment period reported an increase in the velocity of rapid hand movements after treatment with reboxetine and citalopram as well as an improvement in repetitive drawing movements after reboxetine treatment. In turn, Sabbe et al [9] only found an overall cognitive improvement but no motor improvement after 6 weeks of fluoxetine treatment.…”
Section: Introductionmentioning
confidence: 99%